Study on Growth, Structural, Optical and Mechanical nature of L-Threonine Manganese Acetate (LTMA) Single Crystal - Ahamed, N. I.; Anburaj, D. B.; Nedunchezhian, G. (The Nucleus, 2022)
The Novel L-Threonine Manganese Acetate (LTMA) single crystal has been grown successfully by slow evaporation method at 300C. In order to determine the crystalline nature of the samples and cell parameters (a=5.106 Å, b= 7.721 Å, c=13.45 Å & α=β=γ=90 ͦ), Single crystal X-Ray Diffraction and Powder X-Ray Diffraction studies were carried out. The results confirm that drastic changes were observed in the structure of the material. The prominent peaks indicating the positions of the lattice points and crystal planes [111], [411], [422], [431], [444], [552] and [661]. EDAX analysis confirmed the presence of Chemical composition in the crystal. The active functional groups 3169cm-1, 3029 cm-1, 2200 cm-1 of the crystal points were analyzed by FTIR spectrum. Optical nature of the grown crystal obtained by UV-Vis-spectrometry, shows absorption 190nm to 1100nm, transparency in the range of 267-1100 nm and the energy band gap of 4.6eV. Hardness of the LTMA crystal was studied by Vicker’s Micro hardness analyzer. The emission spectrum at 486nm of the grown crystal was determined by Photoluminescence study.